Controle ressonante aplicado à redução de capacitância de barramento em conversores com estágios de potência integrados para alimentação de LEDs a partir da rede CA - Luz, Paulo Cesar Vargas (2017)
This thesis presents a new methodology to reduce bus capacitors in electronic systems with integrated power stages, applied to the LED driver. This reduction is proposed aiming to replace the traditional electrolytic capacitors to others with longer life spam. Through the resonant control of the LEDs current this reduction is possible. The implication of this control technique into the driver input current distortion is modeled. The equation that describes the current absorbed from the mains is obtained to the driver operating in closed loop and with reduced bus capacitor. With this equation it is possible to predict the harmonic content and the quality of the input energy. Detailed design of integrated dual Buck-Boost converter is also presented. A new bus capacitor design methodology is proposed. The experimental results are presented aiming to validate the proposed methodology. It is implemented a prototype to feed 32 LEDs with 700 mA, resulting in approximately 70 W. Through the proposed control technique it was possible to reduce the bus capacitor value by 80%. It is concluded that the proposed control methodology is highly feasible, mainly because it is done only with the change in the converter control law, unlike most of the solutions proposed in the literature.